Copeptin Level After Carotid Endarterectomy and Perioperative Stroke. (February 2014) - Maravic-Stojkovic, Vera; Lausevic-Vuk, L. J.; Obradovic, M.; Jovanovic, P.; Tanaskovic, S.; Stojkovic, B.; Isenovic, R. E.; Radak, D. J.
We evaluated the prognostic value of copeptin levels in a cohort of surgical patients after elective carotid endarterectomy (CEA). Twenty-one patients with perioperative stroke were prospectively recruited. The diagnosis of cerebrovascular event (CVE) was confirmed by computed tomography. Additionally, 21 patients with CEA without any complications (control patients) were enrolled. Blood samples were taken within 3 hours of the symptom onset. Circulating copeptin level was significantly higher in patients with CVE when compared to controls ( P = .025), and significantly higher in nonsurvivors than in survivors ( P = .030) after CVE. Plasma concentrations of interleukin 6 (IL-6) and C-reactive protein (CRP) were also elevated in patients with CVE (IL-6: P = .043; CRP: P = .002). We conclude that the activation of the stress axis in patients with CEA results with copeptin elevation, but more so in patients with perioperative stroke. Copeptin may be a helpful biomarker for stroke risk assessment in patients after CEA.